Grammatical cohesion in legasi Tombiruo Novel by Ramlee Awang Murshid - Ismail, Nazirah; Abdullah, Muhammad Alif Redzuan; Abd Rahim, Normaliza; Kamarudin, Kamariah (Human Resource Management Academic Research Society, 2021)
This study aims to determine conjunctive devices that are found in Legasi Tombiruo novel written by Ramlee Awang Murshid (RAM). This study also analysed the types of conjunctive devices used in the novel to link the sentences, clauses, and paragraphs to become a comprehensive discourse that is capable of leaving a lasting impression on the readers. A qualitative method is employed in this research. Software Atlas ti8 is used to analyse the content of the texts based on the novel as part of the research instrument. The source of this study is a novel entitled Legasi Tombiruo written by Ramlee Awang Murshid. This novel has 530 pages and is analysed based on the application of its words, clauses and sentences. Cohesion theory introduced by Halliday & Hassan (1976) is adopted in this research. Apart from that, types of Malay language conjunctive devices are categorized according to Karim et al (2011). Findings from the research indicate that there are four types of conjunctive cohesion devices which are additive conjunction, adversative conjunction, causal conjunction and temporal conjunction in Legasi Tombiruo novel. This study will facilitate discourse researchers to understand the structural aspect of conjunction devices in Malay Language. It is hoped that the next Malay Language conjunction-based research can provide more focus to conjunction devices apart from grammar, which refers to lexical conjunction.